Analisis Kinerja Keuangan Pemerintah Kota Semarang Tahun 2013-2017 - Efriyani Sumastuti; Eriza Nariyanti; Ika Indriasari (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
The financial performance of local governments is a measure used to ensure the ability of the regions to properly and correctly enforce financial implementation rules to maintain the desired services. This study aims to analyze the financial performance of the local government of Semarang City using 5 financial ratios. The data used is secondary data, in the form of the Semarang City Regional Budget Realization Report in 2013-2017. Furthermore, 5 financial ratios are calculated, consisting of effectiveness ratios, efficiency ratios, compatibility ratios, growth ratios and independence ratios. The results showed that in general the financial performance of the Semarang City local government was very good. This can be seen from the effectiveness ratio of local revenue is very effective, the ratio of regional financial efficiency is very efficient, the ratio of operating expenditure to regional expenditure, the ratio of operating expenditure growth and the growth ratio of capital expenditure has positive growth, the ratio of self-reliance is moderate with participatory relationship patterns. Even so, it is necessary to increase and optimize Regional Original Income (PAD) from year to year through controlling new regional potentials and developing regional potential.